Trends and gaps for integrating lean and green management in the agri-food sector. Issue 5 (25th April 2019) - Muñoz-Villamizar, Andrés; Santos, Javier; Grau, Paloma; Viles, Elisabeth
Abstract : Purpose: The purpose of this paper is to analyze gaps and trends, as well suggest approaches and methodologies that should be addressed by future studies for implementing the lean and green management in the agri-food sector. Design/methodology/approach: Based on a sample with 117 papers, this paper presents a systematic review on the integration of lean and green in the agri-food sector. Findings: Key findings indicate that research on lean and green topics has increased in recent years, an important gap in the integration of lean and green in the agri-food sector has been identified. Two paths that remain open for further research are detected: the lack of theoretical, prescriptive and quantitative research and the possibility of integrating the two most used tools of lean (i.e. value stream mapping) and green (i.e. life-cycle assessment). Practical implications: This study does not only advance the theoretical knowledge of the lean and green field, but it is also beneficial for agri-food companies who aim to effectively deploy lean and green in their processes in order to improve both operational and environmental performances. Social implications: No other industry matches in such a complete way the agri-food industry's challenge of sustainability that is due to the amount of resources it consumes and its interrelatedness with the well-being of humanity. Originality/value: There are separate streams of established research on lean and green management in the agri-food sector, yet very few authors have addressed the intersection of these strategic initiatives.